2021
DOI: 10.12688/f1000research.27284.2
|View full text |Cite
|
Sign up to set email alerts
|

What are the long-term symptoms and complications of COVID-19: a protocol for a living systematic review

Abstract: Although the majority of people with Covid-19 will experience mild to moderate symptoms and will recover fully, there is now increasing evidence that a significant proportion will experience persistent symptoms for months after the acute phase of the illness. These symptoms include, among others, fatigue, problems breathing, lack of smell and taste, headaches, and depression and anxiety. It is also clear the virus has lasting fluctuating multiorgan sequelae, including affecting not only the respiratory system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
3
0
4
Order By: Relevance
“…A considerable proportion of people with acute COVID-19 remain unwell beyond three weeks, although the exact prevalence of ongoing issues among post-COVID-19 patients has not yet been firmly established (1)(2)(3). Knowledge gaps regarding the prevalence of Long COVID are likely owing to several factors, perhaps notably the significant heterogeneity in Long COVID definitions to date (e.g., 'post-acute COVID-19', 'Chronic COVID-19', 'Ongoing symptomatic COVID-19', 'post-COVID-19 syndrome') (4,5), and the fact that Long COVID case recording practices are not commonly used within clinical settings, and certainly not to the same extent that acute-COVID-19 cases are (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable proportion of people with acute COVID-19 remain unwell beyond three weeks, although the exact prevalence of ongoing issues among post-COVID-19 patients has not yet been firmly established (1)(2)(3). Knowledge gaps regarding the prevalence of Long COVID are likely owing to several factors, perhaps notably the significant heterogeneity in Long COVID definitions to date (e.g., 'post-acute COVID-19', 'Chronic COVID-19', 'Ongoing symptomatic COVID-19', 'post-COVID-19 syndrome') (4,5), and the fact that Long COVID case recording practices are not commonly used within clinical settings, and certainly not to the same extent that acute-COVID-19 cases are (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, esforços do Sistema Único de Saúde (SUS) têm sido essenciais para a identificação de casos suspeitos, tratamento, recuperação e cuidados pós-COVID19. Sem as estratégias desempenhadas pelo SUS a proporção da doença poderia ter estendido com proporções mais graves no país 2,3 .…”
Section: Discussionunclassified
“…Diante da discussão abordada no estudo, surge o que podemos denominar de investigação pós-pandemia com foco nas sequelas e complicações causadas pelo Coronavírus. Essa tempestade sintomatológica refuta-se em incógnita pelo fato de os sinais surgirem em caráter leve, moderado ou grave conforme o acometimento de cada caso em específico 3 . Nessa premissa, as investigações pós-hospitalares ganham destaques na medida em que se constrói um novo panorama de cuidados direcionados aos possíveis prejudicados.…”
Section: Duração De Sintomas Por Covid-19 Em Pacientes Pós-internamen...unclassified
“…COVID-19 infection and mortality among healthcare workers followed that of the general population around the world, with 152,888 infections reported during the early phases of the pandemic ( Bandyopadhyay et al, 2020 ). COVID-19 infected individuals may experience long-lasting symptoms for several months after the acute phase of the disease that are not limited to the respiratory system and include, among others, fatigue, headaches, depression and anxiety ( Michelen et al, 2020 ). Post-mortem studies have found a high expression of the angiotensin-converting enzyme 2 (ACE2) transmembrane receptor in the amygdala ( Lukiw et al, 2022 ) and the presence of SARS-CoV-2 RNA in one or more brain regions including the amygdala ( Serrano et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%